Hybrid Requirements Prioritization System Using Cumulative Voting (Cv) And Planning Game (Pg) To Prioritize Requirements In Software Development Project (Cvpg - Priosys) - Said Mohammad Inamul Hafizzan, Saidsaripudin (Universiti Malaysia Sarawak (UNIMAS), 2023)
Requirement Engineering (RE) plays an important role in Software Development Life Cycle (SDLC). RE process helps software development team to deliver high quality system solution. Inside this process there are several key activities in order to develop a successful system. One of them is Requirements Prioritization (RP). The term ―Requirement Prioritization‖ refers to the process of defining the ordering or scheduling for accomplishing requirements according to the priority or importance of those requirements from the viewpoints of the stakeholders. The execution of the RP process in system development may aid the development team in focusing on fulfilling the most critical requirements outlined by the stakeholders‘ desires. Nowadays, there are many techniques that can be applied in prioritizing requirements. Unfortunately, development teams of software have no idea which technique will yield the best outcomes, or when to implement them, because prioritizing could give poorly result if the wrong technique is used. Plus, it is noticeable that there is no technique that excels in every possible scenario. Some techniques may fit well but may not fit for other factors. Scalability, precision, and computation time are just a couple of the parameters that must be fulfilled in order to determine the best method to use. Besides, most of the conventional techniques are implemented manually in which the process is difficult and time consuming like Analytical Hierarchical Process (AHP). Thus, the system solution that will be developed called CVPG – PrioSys. The system is fully automated RP system that will be able to identify the importance of requirements based on the stakeholders‘ selections. The system developed based on the hybrid technique by implementing Cumulative Voting (CV) in Planning Game (PG) will aid the issues of the number of requirements, timeconsuming in execution during RP and accuracy in producing the results of ranked requirements. Moreover, multiple stakeholders will be able to utilize in voting the requirements in one project means that many viewpoints from different stakeholders may be expressed in one place